Design And Application Of Administration Registration A New Student On SDN Wadungasri Sidoarjo - Sulaksanasari Suyoso; Dewiyani Sunarto; Erwin Sutomo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
The registration of new students at SDN Wadungasri, Waru Sidoarjo East Java today is still done manually, which means in the registration of new students are still using systems that are not computerized, which allows the student data errors and takes a long time. In consideration of safety, convenience and storage new student data required making of a new information system that will facilitate the processing of student data in an application of registration of new students as a means of data processing, data storage quickly and precisely.This information system will facilitate and provide convenience for both students and staff of the school of Administration in processing data quickly and prospective students with fewer errors, and transparatif (open) as needed and reliable. The methodology used in the making of this application in the form of observation, interviews and the use of literature. The software used as a tool is database SQL Server 2008 R2 Management Studio and Microsoft Visual Basic .NET 2010. Average required hardware consists of client computers for students and a computer server for the user / division of Administration.The results of the registration application provides convenience in the process of registration of new students and can be done quickly, precisely with minimal errors and cost-effective, ie it only takes 2-3 minutes per person begin enrollment until the class division of the need to manually for 11-15 minutes per person. Also be saving paper use only 2-3 pieces of manually use as much as 8-9 sheets